Avaliação agronômica e caracterização da produção de compostos bioativos em variedades crioulas de pimentas (Capsicum baccatum). - Vasconcelos, Carla Sigales de (2012)
Genetic resources are essential for sustainable development of agriculture and agribusiness. Landraces, improved varieties, advanced lines and native and wild species are comprised in the concept of genetic resources. The diversity found in Capsicum is wide, with a variety of fruit shapes, sizes, colors and flavors, and also with different levels of pungency and nutritional composition. In this context, this study aims to contribute to the genetic resources knowledge of C. baccatum landraces from collection of Active Germplasm Bank of Embrapa Temperate Agriculture. Two papers will be presented with the objectives of characterize and agronomical evaluate C. baccatum landraces, and characterize the genetic variability to produce bioactive compounds in the fruits. 18 accessions of landraces were evaluated using 27 descriptors (14 quantitative and 13 qualitative multicategoric). The statistical analyzes included comparison of means, using clustering by Tocher method for quantitative data, and clustering by Tocher method and UPGMA for qualitative data. Accessions P27 and P179 are recommended for fresh consumption. The access P92 has the highest productivity and pungent fruits that can be used for canning. Access P8 may be recommended for ornamental use due to prostrate growth habit, high density leaves and erect fruit that change color during maturation. The production of phenolic compounds, anthocyanins, total carotenoids and antioxidant activity was evaluated at four points of fruit maturation (0%, 30%, 70% and 100%). The data were subjected to multivariate statistical analysis with principal components analysis. The production of bioactive compounds varied according the different points of maturation. Generally the fully ripe fruit produced higher levels of bioactive compounds. Accession P25 had higher values of anthocyanins for fruits with 30% of maturation, which are violet. Accession P108 showed large variations in antioxidant activity, ranging from 588.44 mg in the unripe fruit to 1373.44 mg in 70% of maturation. To carotenoids the accession P49 varied from 65.03 mg in totally immature fruit to 367.73 mg in 100% maturation. There is great genetic variability in C. baccatum landraces.